Perceived Luxury Value dan Pengaruhnya Terhadap Minat Beli Pada Restoran Mewah di Banjarmasin Kalimantan Selatan - Adista Anjar Diany; Muhammad Risanta; Rika Yuliyanti (Komunitas Dosen Indonesia, 2025)
Restaurants play a role as food providers for the community to fulfil basic human needs. The number of middle to upper class restaurants is also increasing, making companies have to focus on increasing the value of their products. Perceived luxury value is a concept that is an adaptation of customer perceived value. This study aims to determine the effect of functional value, hedonic value, financial value and social influence on purchase intention in luxury restaurants Banjarmasin. The sampling method is non-probability sampling, because the number of luxury restaurant consumers is unknown. The sampling technique was purposive sampling, with 140 respondents. Data analysis using the Structural Equation Model (SEM) method with SMARTPLS 4. Functional value and hedonic value have no significant effect on purchase intention. Meanwhile, financial value and social influence have a significant influence on consumer buying interest in Banjarmasin luxury restaurants. Future research can conduct research on luxury restaurants, especially in other areas, conduct research on other luxury services, and increase the number of respondents.